The National Initiative For Biofuel Development Prospects and Challenges - D.S. Priyarsono (Universitas Trisakti, 2007)
This article reports the current progress and offers some evaluation on the prospects and challenges that may become influential factors in the strategic environment surrounding the national initiative for biofuel development in Indonesia. The prospects include improvement of national energy security, creation of new employment, and proverty reductionr; where as the chalenges include internal factors such as lack of coordination whitin the governmanet, and external uncontrolable factors such as the uncertainty of market condition (demand, supply, prices). This article., expresses personal view and does not necessarily represent the policy of the two institutions.